Product Development and Innovation at Catfish Nugget (Study on Gumuk Bago Hill, Nogosari Rambipuji Village - Maulidiyah, Fany; Tri Cahyaningrum, Deltaningtyas (Journal of Business Management, 2024)
Gumuk Bago Hamlet in Nogosari Village, Rambipuji District, Jember Regency, has natural potential that has not been utilized optimally, such as empty land and river flows only used for irrigation. Researchers introduced the Smart Aquaponic system, integrating the cultivation of catfish and kale plants with IoT technology. Apart from training residents in managing aquaponic products, innovations are being made by processing catfish into nuggets rich in nutrients, which have great potential on the market. This research analyzes the development and innovation strategy for catfish nugget products. Data was collected through interviews, observation, and documentation. The research results show that marketing strategies include improving quality, expanding distribution, and promotions with more attractive packaging designs. The manufacturing process is carried out traditionally without preservatives, however, innovation continues to be developed in the form of flavors and product variants to attract new consumers and maintain market share. In conclusion, the product innovation and marketing strategy succeeded in increasing product adoption and keeping sales growth of catfish nuggets in the local market.